Thermal radiation of heterogeneous combustion products at peat burning - V. A. Kuzmin; I. A. Zagray; R. V. Rukavishnikova (Известия высших учебных заведений: Проблемы энергетики)
Chemical composition, dispersivity and optical properties of peat ash particles are investigated in this paper. Calculation of gas phase components is based on thermal characteristics of the original fuel. Methodology and results of the calculation of the thermal radiation of heterogeneous combustion products at peat burning are given.